2011
DOI: 10.1002/adsc.201000846
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α‐Diazo Carbonyl Compounds with the Shelf‐Stable Diazo Transfer Reagent Nonafluorobutanesulfonyl Azide

Abstract: Nonafluorobutanesulfonyl azide is a shelf-stable, cost-effective and general diazo transfer reagent for the efficient synthesis of a-diazo carbonyl compounds in excellent yields and in very short reaction times, under mild conditions. The diazo products can be readily isolated in pure form after a simple aqueous extractive work-up that avoids chromatographic purification in most cases. Because of its high efficiency and wide substrate scope, shelf-stability, relatively low cost, and ease of product purificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…However, as a valid alternative, numerous sulfonyl azides have been developed for the synthesis of PCDCs. These azides were reported to be superior to tosyl azide in terms of stability, safety, and product purification. , Among them, triflyl azide was shown to be essential for the successful transformation of the nitrophosphonate 41 into diethyl [nitro­(diazo)­methyl] phosphonate ( 42 ) (Scheme ).…”
Section: Synthesis Of λ5-phosphorus-containing α-Diazo Compoundsmentioning
confidence: 99%
“…However, as a valid alternative, numerous sulfonyl azides have been developed for the synthesis of PCDCs. These azides were reported to be superior to tosyl azide in terms of stability, safety, and product purification. , Among them, triflyl azide was shown to be essential for the successful transformation of the nitrophosphonate 41 into diethyl [nitro­(diazo)­methyl] phosphonate ( 42 ) (Scheme ).…”
Section: Synthesis Of λ5-phosphorus-containing α-Diazo Compoundsmentioning
confidence: 99%
“…Ethyl nitrodiazoacetate was synthesized following a known procedure. 5 To a flamedried 50 mL round bottom flask containing a stirbar was added ethyl nitroacetate (2.89 mL, 26.0 mmol) and dichloromethane (10 mL) under Ar. The flask was cooled to 0 ºC and 2,6-lutidine (4.24 mL, 36.4 mmol) was added, followed by NfN 3 (9.30 g, 28.6 mmol).…”
Section: Synthesis Of Ethyl Nitrodiazoacetatementioning
confidence: 99%
“…While we were motivated by the promise of HBD-catalyzed N–H insertion methodologies, the project was initiated with a significant amount of uncertainty as to whether a urea could aid in the decomposition of a diazo compound. The assessment of this approach began with studies of the urea-catalyzed insertion of α-diazo-α-nitro ester 5 into the N–H bond of aniline ( 6 , Table ).…”
mentioning
confidence: 99%
“…We and others have recently shown that nonafluorobutanesulfonyl azide (nonaflyl azide: NfN 3 ) is an efficient, shelf‐stable and cost‐effective24 diazo transfer reagent for the synthesis of azides from primary amines25 and for the preparation of α‐diazo carbonyl compounds 26. We have now explored the use of NfN 3 for the synthesis of sulfonyl azides from readily available sulfonamides and the application of this reaction in a novel copper‐catalyzed two‐step, one‐pot sequential process with added terminal alkynes to afford N , N′ ‐disulfonylamidines.…”
Section: Introductionmentioning
confidence: 99%